Moderate physical training counterbalances harmful effects of low-protein diet on heart: metabolic, oxidative and morphological parameters - Déborah S. Carthagenes; Michelly D. P. Barreto; Cristiane M. Freitas; Anderson da Silva Pedroza; Mariana P. Fernandes; Diorginis S Ferreira; Claudia J. Lagranha; Luciana C. Nascimento; Liriane Baratella Evencio (Motriz: Revista de Educacao Fisica, 2017)
ABSTRACT Aims Maternal low-protein diet induces several impairments on cardiac system. Conversely, moderate exercise has been widely recommended to health improvement due to its effects on heart function. Thus, we investigated whether the moderate physical training is capable to offset the lasting injuries of a maternal protein restriction on the hearts of male adult rats. Methods Pregnant rats were divided into two groups: Control (C=17% casein) and undernutrition (U=8% casein). Offspring from the undernutrition group, at 60 days of life, were subdivided into undernutrition (U) and undernutrition+exercise (UT) groups. Treadmill exercise was performed: (8 weeks, 5 days/week, 60 min/day at 70% of VO2máx). 48 hours after last exercise session, tissues were collected for morphological and biochemical analysis. Results Despite the deleterious effect induced by low-protein diet, physical training was able to restore morphological parameters to similar levels to the control group. Additionally, oxidative stress index was also improved in UT group, due to the increase in antioxidant enzymatic defense. In metabolic enzymes, maternal low-protein diet induced a change in metabolism, and moderate physical training improved oxidative metabolism. Conclusion We demonstrated that moderate physical training can offset the cardiac metabolism in adult rats that were exposed to a maternal low-protein diet.